The Influence of Social and Psychological Factors in the Success of Customer Relationship Management Strategies - Prety Diawati (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2023)
Customer Relationship Management (CRM) is an important business approach in maintaining a strong relationship between a company and its customers. CRM strategies aim to increase customer satisfaction, build loyalty, and maximise customer value. This study aims to analyse the influence of social and psychological factors in the success of CRM strategies. This research is a literature review that adopts a qualitative method approach, which means that this research will analyse and interpret data by relying on information and text from various sources. The study results show that in a competitive business world, CRM plays an important role in building strong relationships with customers. Social and psychological factors have a crucial influence on the success of CRM strategies. Strong interpersonal relationships with customers are key, and companies should pay special attention to training employees to interact well and empathetically.